Understanding Academic Procrastination Through a Moderated Mediation Framework: Examining Self-Efficacy, Motivation, and Self-Regulated Learning - Dwi Nor Anisah; M. Fathur Rahman (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to analyze the influence of academic self-efficacy and learning motivation on academic procrastination with self-regulated learning as a mediating variable and academic pressure as a moderation variable. This study uses a quantitative approach with an explanatory method. The population of this study is all students of grade XI Social Studies with a sample of 124 students determined by simple random sampling technique. Data collection used a likert scale questionnaire and analyzed with Structural Equation Modeling (SEM-PLS). The results of the study showed that academic self-efficacy and learning motivation had a negative and significant effect on academic procrastination. Self-regulated learning has a significant effect and has been proven to mediate the relationship between academic self-efficacy and learning motivation to academic procrastination. In the moderation test, academic pressure did not moderate the relationship between academic self-efficacy and academic procrastination, but it strengthened the relationship between learning motivation and academic procrastination. This finding indicates that learning motivation is more responsive to academic demands, whereas academic self-efficacy tends to function as a relatively stable internal belief. These findings contribute to the development of adaptive learning strategies oriented towards student learning independence.